Upaya Meningkatkan Hasil Belajar Matematika dengan Metode STAD Siswa Kelas XII MA Darusslam Manuju - Nur Aisyah; Azwan Anwar; Anriani Anriani (Lembag, 2024)
This research is classroom action research (PTK) carried out at MA Darusslam Manuju which aims to improve mathematics learning outcomes using the STAD method. The subjects of this research were 30 class XII students. Data collection was carried out using learning outcomes tests. The collected data was analyzed using quantitative and qualitative analysis. The research results showed that the average score of student learning outcomes in cycle I reached an average of 78.77 and in cycle II reached an average of 81.37. The standard deviation in cycle I was 2,674 and in cycle II was 1,829. Keywords:,